From a philosophical point of view : selected studies - White, Morton, 1917-2016 (Princeton University Press, 2005)
One of the most important philosophers of recent times, Morton White has spent a career building bridges among the increasingly fragmented worlds of the humanities, social sciences, and natural sciences. From a Philosophical Point of View is a selection of White's best essays, written over a period of more than sixty years. Together these selections represent the belief that philosophers should reflect not only on mathematics and science but also on other aspects of culture, such as religion, art, history, law, education, and morality. White's essays cover the full range of his interests: studi.